Pengaruh pencapaian kepuasan konsumen rumah makan berdasarkan kesan kualitas produksi dan harga - Eli Retnowati; Rahayu Mardikaningsih; Didit Darmawan; Ella Anastasya Sinambela (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
The increasing development of the restaurant industry causes competition between business people, each business actor. This study was conducted to analyze and discuss the role of product quality impressions and price impressions on consumer satisfaction who visited the "Ayam Bakar Wong Solo" restaurant. The sampling technique in qualitative research uses non-probability sampling. The population in this study were all consumers who had eaten at the "Ayam Bakar Wong Solo" restaurant in the city of Surabaya, with 100 responden being a sampel. This study using multiple linear regression bassed the statistical analyze which is helped by SPSS 25.0 application. The results showed that the impression of product quality and the impression of price had a significant effect on the satisfaction of consumers who had visited the restaurant.